OS PROGRAMAS DE TRANSFERÊNCIA DE RENDA DO MUNICÍPIO DE PONTA GROSSA: BENEFÍCIO DE PRESTAÇÃO CONTINUADA –BPC E BOLSA FAMÍLIA, COMO AÇÕES DE ENFRENTAMENTO DA POBREZA - Wlodarski, Regiane (2007)
Brazilian society is marked by social inequality and the high poverty rate which are related to the economical, political and social development model adopted in the country. Poverty in Brazil comes from the high social inequality rates which are due to the irregular process of wealth distribution. Poverty is constructed and consolidated as a result of the ways men are organized in society and it exclude the population from the access to goods and services, to the social relations and to right of citizenship. In this way, it is necessary intervention of the State, as a social regulatory institution, offering to the whole population access to goods and services through out social policies. These actions, directed by the public policies, are often the only way of insertion to the access to goods and services and to citizenship. It increases the discussion about the formulation of actions for the population with the right and principally, the population which is in poverty, taking into consideration the needs of the population, getting to know the reality of these people, to reach their goals. The proximity with the poverty theme and the vision of its problems in the city of Ponta Grossa – Paraná which, according to the Demographic Census of 2000, has 12 000 families in poverty, being the second city of the State of Paraná in number of shanty towns, led to the development of the study, which wants to analyze: the income transferring programs in the city of Ponta Grossa, Benefício de Prestação Continuada – BPC and Bolsa Família, as actions to face poverty. From the proposed object, it was tried to understand how these programs have being carried out in the city and to know better which is the population that is in poverty, where this population is located, who are the actions of income transferring directed to in the city and how these actions help to face poverty.